PERBEDAAN JENIS PAKAN TERHADAP PERTAMBAHAN BOBOT BADAN DAN MORTALITAS KELINCI DI KABUPATEN BLITAR - Vito Setia Nanda; Nita opi ari kustanti; Agustina Widyasworo (Universitas Islam Balitar, 2019)
This research was conducted to determine the weight gain and mortality of rabibits with different types of feed. The method used is proposive sampling by participating in direct observation and being actively involved in this farming activity, especially those releted to the analysis of meat rabbit production located in Blitar Regency. From the results of research conducted on 30 rabbits, the difference in body weight gain between the first treatment using concentrate and the second treatment using forage had a significant difference. By using concentrate feed, three was a mortality of 0.15 during maintenance. Whereas in the treatment using forage, there was a mortality of 0.36. Body weight gain in rabbits treated with concentrate feed experienced a significant rate of increase. From the results of the research conducted, different types of feed have an effect on weight gain and mortality of rabbits